2018
DOI: 10.1002/jlb.3mir0817-337r
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulators that mediate ocular immune privilege

Abstract: The ocular microenvironment has adapted several negative regulators of inflammation to maintain immune privilege and health of the visual axis. Several constitutively produced negative regulators within the eye TGF-β2, α-melanocyte stimulating hormone (α-MSH), Fas ligand (FasL), and PD-L1 standout because of their capacity to influence multiple pathways of inflammation, and that they are part of promoting immune tolerance. These regulators demonstrate the capacity of immune privilege to prevent the activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
60
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 142 publications
3
60
0
Order By: Relevance
“…A well-controlled system to regulate the inflammatory response in the eye is necessary. 35 We reported that Bacillus reach their maximum growth faster than most other Gram-positive endophthalmitis pathogen in the eye. 9 Bacillus endophthalmitis is well recognized for creating an aggressive acute inflammatory response that results in retinal damage with rapid loss of vision within 12 to 24 hours, even as antibiotic and antiinflammatory treatment is given.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A well-controlled system to regulate the inflammatory response in the eye is necessary. 35 We reported that Bacillus reach their maximum growth faster than most other Gram-positive endophthalmitis pathogen in the eye. 9 Bacillus endophthalmitis is well recognized for creating an aggressive acute inflammatory response that results in retinal damage with rapid loss of vision within 12 to 24 hours, even as antibiotic and antiinflammatory treatment is given.…”
Section: Discussionmentioning
confidence: 91%
“…During infection, ocular immune privilege 35 is compromised by an overwhelming, acute inflammation resulting from interactions between innate receptors and microbial ligands. We reported that Toll-like receptors (TLR) 2 and 4, but not TLR5, were necessary for robust intraocular inflammation during Bacillus infection.…”
mentioning
confidence: 99%
“…Several soluble and cell-bound inhibitory factors are involved in the mechanism of ocular immune privilege to create an intraocular immunosuppressive microenvironment, which prevents excessive immune activation and subsequent tissue damage. These factors include transforming growth factor-beta (TGF-β)2 (15), retinoic acid (16), and multiple immunosuppressive factors in ocular fluids (17), and the constitutive expression of the Fas ligand (18), programmed death-ligand 1 (PD-L1) (19), galectins (20), membrane glycoprotein CD200 receptor 1 (21), cytotoxic T lymphocyte-associated protein (CTLA)-2a (22), B7 (23,24) on the surface of ocular cells. For the maintenance of retinal homeostasis, these immunosuppressive molecules in the eye actively regulate the induction and the expression of inflammation to prevent excessive activation and subsequent tissue damage.…”
Section: The Normal Immunological Condition In the Eyementioning
confidence: 99%
“…This blood-retinal barrier permeability and neutrophil infiltration into a normally immune privileged environment is detrimental to vision. The immune response in the eye is tightly regulated --the vitreous is avascular, there is a lack of lymphatic vessels and antigen presenting cells, and immunosuppressive factors are present[45][46][47]. Bacterial endophthalmitis and other ocular diseases with inflammation compromise immune privilege.…”
mentioning
confidence: 99%